2023
DOI: 10.3389/fcimb.2023.1146381
|View full text |Cite
|
Sign up to set email alerts
|

The innate and T-cell mediated immune response during acute and chronic gammaherpesvirus infection

Abstract: Immediately after entry into host cells, viruses are sensed by the innate immune system, leading to the activation of innate antiviral effector mechanisms including the type I interferon (IFN) response and natural killer (NK) cells. This innate immune response helps to shape an effective adaptive T cell immune response mediated by cytotoxic T cells and CD4+ T helper cells and is also critical for the maintenance of protective T cells during chronic infection. The human gammaherpesvirus Epstein-Barr virus (EBV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 222 publications
(221 reference statements)
0
7
0
Order By: Relevance
“…The antiviral innate immune response sets in motion all the main components of the adaptive immune response: the cytotoxic CD8+ T cells, CD4+ T helper cells and antibody-producing B cells. While CD8+ cells have the ability to directly attack and get rid of the infected cells, CD4+ cells mediate immune responses through the secretion of specific cytokines [ 64 ]. This response is exemplary in acute IM, which has a characteristically exaggerated expansion of CD8+ T cells that are mostly specific for EBV lytic phase antigens and can account for up to almost 50% of all blood circulating lymphocytes [ 65 , 66 ].…”
Section: Specific Immune Response To Ebvmentioning
confidence: 99%
“…The antiviral innate immune response sets in motion all the main components of the adaptive immune response: the cytotoxic CD8+ T cells, CD4+ T helper cells and antibody-producing B cells. While CD8+ cells have the ability to directly attack and get rid of the infected cells, CD4+ cells mediate immune responses through the secretion of specific cytokines [ 64 ]. This response is exemplary in acute IM, which has a characteristically exaggerated expansion of CD8+ T cells that are mostly specific for EBV lytic phase antigens and can account for up to almost 50% of all blood circulating lymphocytes [ 65 , 66 ].…”
Section: Specific Immune Response To Ebvmentioning
confidence: 99%
“…An overview of MHV-68-associated pathogenesis in mice and the interaction with the host was provided previously [ 81 ]. More recently, the features of innate and T cell responses in the context of MHV-68 infection in mice and their relevance for EBV were summarized [ 82 ].…”
Section: Mouse Herpesvirus Orthologues As Models For Beta- and Gammah...mentioning
confidence: 99%
“…Skin xenograft models confirmed that infected T cells can release infectious virions in vivo [ 82 , 134 , 135 ]. Notably, VZV infection also induced slow progression of typical skin lesions and was associated with a robust innate immune response of epidermal cells in the skin [ 153 ].…”
Section: Investigating Human Herpesviruses In Human Cell-engrafted Micementioning
confidence: 99%
“…EBV has evolved numerous techniques for manipulating the IFN response, thus enhancing its immunoevasive capabilities ( 179 ). One protein that contributes to downregulation of the IFN response is the early protein BFRF1 ( 180 ).…”
Section: Modulation Of T Cell Response and Implications For Cancer Ce...mentioning
confidence: 99%